Strain-rate-dependent mechanics and impact performance of epoxy-based nanocomposites - Tüfekci, Mertol; Özkal, Burak; Maharaj, Chris; Liu, Haibao; Dear, John P.; Salles, Loïc (Elsevier, 2023)
Strain-rate-dependent mechanical properties and impact performance of manufactured epoxy-based nanocomposites are investigated. As reinforcements, fumed silica (FS) and halloysite nanotube (HNT) are used alongside Albipox 1000 and Nanopox F700. First, the internal structures of the composites are visualised using scanning electron microscopy (SEM). To identify the strain-rate-dependent mechanical properties, three-point bend tests are conducted at three different strain rate levels. For the impact resistance, Charpy impact tests are performed. For further investigations of the mechanical properties of the composites, mean-field homogenisation (MFH) and finite element (FE) analyses on the representative volume elements (RVE) are performed for each type of composite material. Overall, the modelling and experiments are in good agreement and account for the mechanical behaviour of these epoxy-based nanocomposites.
Keywords: Nanocomposites; Mechanical characterisation; Nonlinear behaviour; Strain-rate-dependence; Numerical simulation